Shapeshifting Nanocatalyst for CO2 Conversion. - Girotto, Gustavo Zottis ; 0000-0002-9251-4409; Jaugstetter, Maximilian; Kim, Dongwoo; Matte, Lívia P; Mishra, Tara P; Scott, Mary; Martins, Ruan M; Muniz, André R; Salmeron, Miquel; Nemsak, Slavomir; Bernardi, Fabiano (Advanced Materials, 2025)
The conversion of CO 2 into high-value chemicals through a photoreduction reaction in water is a promising route to reduce the dependence on fossil fuels. Enhancing selectivity toward hydrocarbons or alcohols can be achieved by Ag-Cu alloys. However, the stabilized surface state created by Ag-Cu interactions is still poorly understood. In this work, multi-modal in situ X-ray experiments reveals underlying mechanisms and the evolution of Ag-Cu nanoparticles under CO 2 reduction reaction (CO 2RR) conditions. Both morphological and chemical changes of Ag and Cu species induced by diffusion mechanics are tracked during nanocatalyst operation. The initial spheroid Ag-Cu nanoparticles are composed of a Cu-rich shell and Ag-rich core. The reduction treatment promotes Ag migration toward the surface. During photocatalytic CO 2 reduction reaction, Cu atoms migrate back to the surface, forming Ag-Cu-O species. The study observes the surface oxidation of Cu(0) to Cu + and the presence of Ag at the sub-surface region. Furthermore, nanoparticles change their shape, decreasing their specific surface area, driven by Cu diffusion during the CO 2 photoreduction reaction. The results provide invaluable insights into the dynamic restructuring of the catalyst under reaction conditions and into the active species responsible for CO 2 conversion.
© 2025 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.